2009
DOI: 10.1080/02508281.2009.11081603
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder Participation in Tourism Destination Planning Another Case of Missing the Point?

Abstract: A legacy of adverse impacts from tourism activity has led to widespread, and generally well accepted, calls for multiple stakeholder groups, in particular the resident community, to participate in the process of planning tourism activity within a destination. While this notion has infiltrated the rhetoric of governments' worldwide, authors have questioned the extent to which stakeholder participation actually occurs in tourism destination planning practice. Indeed, some authors have claimed that despite the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 67 publications
0
11
0
7
Order By: Relevance
“…Fraser et al [3] note that the benefits of participation are felt most strongly if stakeholders are truly incorporated into decision making and final results, and are made more relevant for policy makers. Opponents to this approach are sceptical as they find involvement to be tokenistic [4] or even a simplistic way of creating an illusion of responsibility [5]. Considering this variety in opinion, the perception may also be the result of the respective planning approach and significantly influenced by the circumstances, the timeframe and the provided framework.…”
Section: Introductionmentioning
confidence: 99%
“…Fraser et al [3] note that the benefits of participation are felt most strongly if stakeholders are truly incorporated into decision making and final results, and are made more relevant for policy makers. Opponents to this approach are sceptical as they find involvement to be tokenistic [4] or even a simplistic way of creating an illusion of responsibility [5]. Considering this variety in opinion, the perception may also be the result of the respective planning approach and significantly influenced by the circumstances, the timeframe and the provided framework.…”
Section: Introductionmentioning
confidence: 99%
“…In a similar research, Ruhanen (2009) found that during the creation of city tourism developmental plans not all stakeholders of a certain destination participated, among which the local population was not significantly or not at all involved. Barrutia and Echebarria (2015) also point to insufficient local population involvement, which they support by the fact that the locals have too little power to achieve their goals due to institutional barriers and slow implementation, and therefore participate relatively indifferently in the pre-defined developmental plans.…”
Section: Assumptions For Successful Implementation Of the Sustainablementioning
confidence: 95%
“…The operationalization of the sustainable tourism development concept depends on a defined plan within which sustainable development goals should be set to define the administrative structure and partners, determine the ac-Neki gradovi su prepoznali važnost planiranja razvoja turizma, poput grada Barcelone (Španjolska) koji je od 1990. do 2003. godine izradio i proveo četiri strategije razvoja turizma (d 'Angella, 2007). Istovremeno, Ruhanen (2009) je u Australiji utvrdila postojanje razvojnih planova turizma samo kod 30 od 125 uprava gradova. Međutim, stvarna uspješnost strategija je upitna, jer proces izrade (formulacije) strategije nije zahtjevan naspram njene praktične primjene za koju nedostaju potrebna znanja (Ruhanen, 2008).…”
Section: Assumptions For Successful Implementation Of the Sustainableunclassified
See 1 more Smart Citation
“…De forma geral, o debate em torno da governança nos destinos turísticos vem ganhando cada vez mais destaque (Laws et. al., 2011) considerando a importância dos processos de cooperação interorganizacional no planejamento do turismo (Jamal & Getz, 1995;Thimothy, 2010), como também a necessidade da efetiva participação dos stakeholders no processo (Ruhanen, 2009).…”
unclassified